2021
DOI: 10.1002/slct.202101900
|View full text |Cite
|
Sign up to set email alerts
|

Potential Use of DMSA‐Containing Iron Oxide Nanoparticles as Magnetic Vehicles against the COVID‐19 Disease

Abstract: Iron oxide magnetic nanoparticles have been employed as potential vehicles for a large number of biomedical applications, such as drug delivery. This article describes the synthesis, characterization and in vitro cytotoxic in COVID-19 cells evaluation of DMSA superparamagnetic iron oxide magnetic nanoparticles. Magnetite (Fe 3 O 4 ) nanoparticles were synthesized by co-precipitation of iron salts and coated with meso-2,3dimercaptosuccinic acid (DMSA) molecule. Structural and morphological characterizations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 48 publications
(95 reference statements)
0
11
0
Order By: Relevance
“… Successfully developed and physiochemically characterized NPs showed good biocompatibility against normal cell lines. [152] Hamouda et al, AgNPs fabricated wearing mask Antiviral activity and breathability performance AgNPs exhibited less toxicity with immense viral inhibitory potentiality. AgNPs fabricated cotton mask showed better air permeability and breathability compared to surgical mask.…”
Section: Nanoparticles For Therapeutic Drug Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“… Successfully developed and physiochemically characterized NPs showed good biocompatibility against normal cell lines. [152] Hamouda et al, AgNPs fabricated wearing mask Antiviral activity and breathability performance AgNPs exhibited less toxicity with immense viral inhibitory potentiality. AgNPs fabricated cotton mask showed better air permeability and breathability compared to surgical mask.…”
Section: Nanoparticles For Therapeutic Drug Deliverymentioning
confidence: 99%
“…Thus developed DMSA-Fe 3 O 4 NPs with a size range of 12 nm were physiochemically and magnetically characterized using different techniques owing to optimally synthesized for delivery. Moreover, a biocompatibility study of DMSA-Fe 3 O 4 NPs further demonstrated the lack of toxicity to a normal cell, providing new insight for use of Nano-medicinal based delivery to mitigate the deadliest COVID 19 [152] .…”
Section: Nanoparticles For Therapeutic Drug Deliverymentioning
confidence: 99%
“…130 Furthermore, the free thiol and carboxylic groups of DMSA can be conjugated with antibodies, proteins or other drugs for biomedical applications. 129 However, Liu et al reported that DMSA coated MNPs could degrade into iron ions in an acidic environment inside the lysosome. 131 This degradation will result in high concentration of iron accumulated in the body that can produce reactive oxygen species and thus lead to cell toxicity.…”
Section: Surface Modification Of Mnp For Mpimentioning
confidence: 99%
“…DMSA coated NPs have excellent biocompatibility, show no signs of cytotoxicity and can achieve high stability in biological media for up to 6 months. 26,84,129 In a recent study conducted ▣Citoglu et al, it was reported that 25 nm cubic SPIONs coated with DMSA possess a higher magnetisation compared to unmodified SPIONs (coated with decanoic acid). 130 The increase in M sat (DMSA coated = 89.6 emu g −1 and unmodified = 74.2 emu g −1 ) is hypothesised to be due the disulfide bonds from the DMSA molecule that can shorten the distance between MNPs and hence improve the magnetic properties (Fig.…”
Section: Stabilisation Of Mnps Against Aggregationmentioning
confidence: 99%
“…Figure 6 taken from (Chenthamara et al, 2019) provides a broader perspective on the different roles of iron oxide nanoparticles for biomedical applications. Potential toxic effects of IONPs have been investigated and further research needs to be performed before its consideration as an effective therapeutic against viral pathogens like SARS-CoV-2 and as drug delivery agents (Martins et al, 2021). In 2011, an experiment was performed where the toxic effects of IONPs were tested for both in vivo (Wistar rats) and in vitro environments (Szalay et al, 2012).…”
Section: Using Inorganic Nanoparticlesmentioning
confidence: 99%